IoT-Based Smart Dustbin Prototype - Andi Muhammad Saad; Badillah Ode Jul; Abdullah Basalamah; Saidah Sayuti (Program Studi Teknik Elektro Universitas Khairun, 2023)
Increasing population and consumption patterns affect the volume, type, and characteristics of waste which vary and increase periodically. This increment must be accompanied by the management of waste transportation so that the accumulation of waste can be prevented. Therefore, it is necessary to design a prototype of a smart dustbin condition monitoring tool that is capable of providing full information and notifying the collector in the form of the location of the IoT-based dustbin. The research method is a prototyping type to obtain a smart dustbin prototype and produces IoT-based smart dustbin hardware and software. Ultrasonic sensors are used to detect objects and measure the height of waste, loadcell sensor measure the weight of waste, and GPS is used to obtain the location of dustbin. NodeMCU ESP8266 processes sensor data and sends it to the user. The results showed that testing of the object detection hardware was able to open and close the dustbin automatically when there was an object at a distance of â‰¤50 cm. Detectors of height and weight of waste can measure the height and weight of waste with an error of 0.4% and 0.15% respectively. The results of software testing show that the tool succeeds in sending WhatsApp notification data when the waste height reaches 3 cm from the sensor or 4000-gram waste weight, with a Throughput measurement of 327.95 kbps, and takes 2.61 seconds to send a notification message of 69 bytes.